Pengaruh Fraksi Volume Terhadap Sifat Mekanis Komposit Forged Fiberglass Metode Compression Mould - Muhammad Fakhruddin; Imam Mashudi; Mochamad Muzaki; Hilmi Iman Firmansyah; Bayu Pranoto; Hangga Wicaksono (Polinema Press, Politeknik Negeri Malang, 2022)
Fiber-reinforced composites can be classified into two parts, namely short fiber composites and long fiber composites. Long fibers are stronger than short fibers. Long fiber (continuous fiber) is more efficient in laying than short fiber but short fiber is easier to lay than long fiber. Fiber length affects the processability of the fiber composite. Judging from the theory, long fibers can continue the load and stress from the stress point to the other fiber. In this study, the volume of chopped glass fiber composite with random matrix direction was varied with respect to polyester resin. Making forged fiberglass composites with the press mold method to minimize the occurrence of air bubbles during the composite molding process. Testing the mechanical properties of the forged fiberglass composite using the three-point bending and tensile testing methods. The expected result is the variation of the volume fraction of random chopped glass fiber to polyester resin. The TKT to be achieved from this research is TKT level 3, which is an analytical study that supports the prediction of the performance of the effect of the volume fraction between glass fiber and resin on the mechanical properties of the tensile and bending strength of forged glass fiber composites